(untitled) (Research, Society and Development, 2020)
The general objective of the article is to present the socioeconomic data of the students of the Brazil Test 2015 of the 5th year of the State of Rio Grande do Sul. The specific objectives are to illustrate the data by means of graphs and to analyze the influence of socioeconomic conditions on the habits of students reading. The methodology is quantitative / qualitative and the data source is the contextual questionnaire of the National System of Evaluation of Basic Education (SAEB-2015), of the 5th year of public schools in the State of Rio Grande do Sul. Data were collected from the National Institute of Educational Studies and Research Anísio Teixeira (INEP). From the sociocultural data, it was verified that the predominant ethnicity in the State is white with 48% (27,841) of the students, due to the European immigrant process. And, among the quantified socioeconomic data it is highlighted that, most of the families can obtain basic utensils, however, there are restrictions in the acquisition. Finally, it was inferred that the influence of the family and the quality of family life creates perspectives and thus the development of language and the logical-mathematical reasoning that are instigated in children from the play.